2017
DOI: 10.1148/rg.2017160166
|View full text |Cite
|
Sign up to set email alerts
|

Internal Thoracic Lymphadenopathy in Breast Cancer

Abstract: The internal thoracic (IT) nodal basin is a first-echelon drainage pathway in the breast, accounting for up to a quarter of its lymphatic drainage, primarily from the deep structures of the breast. The presence of internal thoracic node (ITN) metastases upstages the breast cancer (BC) patient to a minimum of clinical stage III disease. Medial tumors, deep tumors, young age, axillary nodal metastases, tumors of a high nuclear grade, lymphovascular invasion, and triple-negative hormone receptor status are predis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Malignancies affecting lymph nodes account for secondary localisation of thoracic or extrathoracic malignancies (metastasis of lung cancer, digestive cancer or gynaecological malignancies) or primary nodal lesions (haematological malignancies) [87][88][89].…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…Malignancies affecting lymph nodes account for secondary localisation of thoracic or extrathoracic malignancies (metastasis of lung cancer, digestive cancer or gynaecological malignancies) or primary nodal lesions (haematological malignancies) [87][88][89].…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…The prognostic role of regional LAP in several malignancies has been considered in previous studies (30,31) and reviews (32). Cahoon et al (32) indicated that understaging of internal thoracic LAP in patients with breast cancer significantly impacted patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The IMN is situated in the parasternal region surrounded by the interpectoral muscle, fibrofatty tissue, and the internal mammary vessels [10]. As the IMN is located in narrow intercostal spaces adjacent to the internal mammary vessels, it is difficult to perform a biopsy the IMN.…”
Section: Discussionmentioning
confidence: 99%